A new variety of Brachystelma maculatum (Apocynaceae) from Andhra Pradesh, India - Nagendra, C.; Nagaraju, V.; Madhusudhana Reddy, A.; Prasad, K. (Rheedea, 2026)
A new variety of Brachystelma maculatum Hook.f. is described from Anantapuram district of Andhra Pradesh, India. A detailed description, photographs and conservation status are provided for the new variety.